Using PubChem’s database with data mining and machine learning algorithms for the prediction of EGFR inhibitors: a comparative study - Rosa, Liliana Monteiro (2018)
Dissertation presented as the partial requirement for obtaining a Master's degree in Information Management, specialization in Knowledge Management and Business Intelligence